تفعيل مبادئ الحوكمة كآلية لمكافحة الفساد المالي – تجارب دولية ناجحة – - سارة عميور; جيهان حيدري (My University, 2022)
This study aims to highlight the extent of the contribution of activating the principles of governance in combating financial corruption, based on the presentation of the most important successful international experiences in this field. According to the Corruption Perceptions Index issued by Transparency In addition to extracting the most .International for the period (2010-2021) important lessons from these experiences to benefit from them in the fight against financial corruption in Algeria, as this phenomenon has become widespread in Algeria in recent years. In this study, a number of results were reached, the most important of which is that activating the principles of governance, in addition to other efforts, plays a significant role in combating financial corruption in the countries under study. However, both the Singaporean experiment and the U. S. A experiment are considered pioneering experiences in this field. As for the Egyptian experience, it still needs more attention and development, because most of the regulations governing its governance are indicative, not mandatory. ........................................... تهدف هده الدراسة إلى إبراز مدى مساهمة تفعيل مبادئ الحوكمة في مكافحة الفساد المالي استنادا إلى عرض أهم التجارب الدولية الناجحة في هذا المجال، و ذلك بتحليل هذه التجارب حسب مؤشر مدركات الفساد الصادر عن منظمة الشفافية العالمية 2221 (، بالإضافة إلى استخلاص أهم الدروس من هذه التجارب للاستفادة منها في مكافحة الفساد المالي في - للفترة) 2212 الجزائر لاستشراء هذه الظاهرة بشكل كبير في الجزائر في السنوات الأخيرة. وقد تم التوصل في هذه الدراسة إلى مجموعة من النتائج أهمها أنه لتفعيل مبادئ الحوكمة إضافة إلى جهود أخرى دور كبير في مكافحة الفساد المالي في الدول محل الدراسة، إلا أن كل من التجربة السنغافورية و تجرية الولايات المتحدة الأمريكية تعد من التجارب الرائدة في هذا المجال. أما التجربة المصرية مازالت بحاجة إلى المزيد من الاهتمام و التطوير، لأن أغلبية اللوائح المنظمة للحوكمة بها عبارة عن لوائح إرشادية لا إلزامية.